Diversifikasi Produk Olahan Melinjo Dalam Peningkatan Perekonomian Masyarakat - Fitri Nurlaili (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2019)
The aim of this Community Service program was to improve the economy of the society of Sangiang Village, Mancak District by providing knowledge and skills about diversification processing processed products of melinjo seeds. Service was carried out in several stages survey, socialization, procurement, packaging, labeling and promoting. The result of this dedication was the increase in society knowledge and skills regarding the processing of melinjo seeds into a variety of flavor variants that have not been done in Sangiang Village. This program was expected to improve the economy of the society by being able to increase the selling value of Melinjo products.